The need for continuous compliance. Issue 6 (June 2018) - Khan, Javid
Abstract : Compliance isn't a new challenge to business. In fact, it is something that organisations have been grappling with for some time, particularly those in highly regulated industries such as insurance and financial services. However, with the new EU General Data Protection Regulation (GDPR), the need for businesses to remain compliant with increasingly stringent industry regulations has once again come into focus.